Peran Motivasi Terhadap Prestasi Belajar Anak di SMP Al-Madina Wonosobo - Hanifah Dwi Rahayu; Sri Haryanto; Salis Irvam Fuadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this writing is to find out: 1) Children’s learning motivation strategies for successful learning at al-Madina Middle School, Wonosobo, 2) To find out the role of motivation in children’s learning success at Al-Madina Middle School Wonosobo, 3) To find out the supporting and inhibiting factors.Learning motivation on children’s learning success at Al-Madina Middle School, Wonosobo. This research uses a qualitative approach with the type of field research. Data collection techniques use observation, interview and documentation methods. The data analysis technique used is: Milles Huberman data analysis and triangulation. The results of the research show that: 1) The strategy to increase learning motivation in learning activities at Al-Madina Middle School, Wonosobois an effort to increase student learning motivation in learning activities in order to improve student learning achievement, 2) Form the role of motivation in children’s learning success at Al-Madina Middle School Wonosobo, namely: improving the student understanding process, and increasing student motivation. Enable students to be creative and take initiative in their learning, 3) The role of motivation in children’s learning achievement at Al-Madina Middle School includes inhibiting and supporting factors, including: Inhibiting factors, namely student health, student psychology, sense of learning,learning technology, infrastructure, parental or family factors and student interest in learning. The supporting factors are fun media and teaching methods and teaching and learning supporting activities.